Immunity to Chlamydia trachomatis Mouse Pneumonitis Induced by Vaccination with Live Organisms Correlates with Early Granulocyte-Macrophage Colony-Stimulating Factor and Interleukin-12 Production and with Dendritic Cell-Like Maturation - Zhang, Dongji (American Society for Microbiology, 1999)
As is true for other intracellular pathogens, immunization with live Chlamydia trachomatis generally induces stronger protective immunity than does immunization with inactivated organism. To investigate the basis for such a difference, we studied immune responses in BALB/c mice immunized with viable or UV-killed C. trachomatis mouse pneumonitis (MoPn). Strong, acquired resistance to C. trachomatis infection was elicited by immunization with viable but not dead organisms. Immunization with viable organisms induced high levels of antigen-specific delayed-type hypersensitivity (DTH), gamma interferon production, and immunoglobulin A (IgA) responses. Immunization with inactivated MoPn mainly induced interleukin-10 (IL-10) production and IgG1 antibody without IgA or DTH responses. Analysis of local early cytokine and cellular events at days 3, 5, and 7 after peritoneal cavity immunization showed that high levels of granulocyte-macrophage colony-stimulating factor and IL-12 were detected with viable but not inactivated organisms. Furthermore, enrichment of a dendritic cell (DC)-like population was detected in the peritoneal cavity only among mice immunized with viable organisms. The results suggest that early differences in inducing proinflammatory cytokines and activation and differentiation of DCs may be the key mechanism underlying the difference between viable and inactivated organisms in inducing active immunity to C. trachomatis infection.